Predicting Equations and Resting Energy Expenditure Changes in Overweight Adults - Stubelj Mojca; Teraž Kaja; Poklar Vatovec Tamara (Sciendo, 2019)
The aim of the study is to show the differences between the measured and estimated values of resting energy expenditure and any changes occurring after the 6-month weight loss intervention program.